Grain Size and Macrosegregation Control of Large-Sized AA2219 Billets by Internal Electromagnetic Stirring in DC Casting - Zhao, Haodong; Zhang, Zhifeng; Li, Bao; Bai, Yuelong; Gao, Mingwei (Frontiers in Materials, 2022)
This work focuses on the effect of internal electromagnetic stirring (IEMS) on grain size and macrosegregation in direct chill (DC) casting of AA2219 billet 880 mm in diameter. The IEMS process has been applied to provide the forced convection within the solidifying melt to achieve an efficient reduction of mean grain size and alleviate the formation of macrosegregation. Two casting electromagnetic parameters (the stirring electric current and frequency) of the IEMS process were applied to assess the uniformity of microstructure and macrosegregation of the billet. The results obtained show that finer and more uniform grains in the billet prepared by the IEMS process than that of traditional DC casting have been observed. And the IEMS had a great influence on the improvement of the macrosegregation but the greater electromagnetic fields would result in worse macrosegregation in the center of the billet.